Plus Bhutto's Episode : An Autobiography - Rahat Latif, Maj. Gen. (Retd) (Lahore Mavara Publishers, 2004)
Autobiography of a retired major general of Pakistan Army, with particular reference to his assignment as Martial Law sub-administrator, Rawalpindi, where former prime minister Zulfikar Ali Bhutto was imprisoned.
Include Appendix, Illustrations and Notes.
Keywords: Pakistan -- Bhutto, Zulfikar Ali, 1928-1979